\(a=\cfrac{\sqrt5+1}{\sqrt5-1}\) এবং \(b=\cfrac{\sqrt5-1}{\sqrt5+1}\) হলে \(\cfrac{a^2+ab+b^2}{a^2-ab+b^2}\) এর মান নির্ণয় করো । Madhyamik 2012


\(a+b=\cfrac{\sqrt5+1}{\sqrt5-1}+\cfrac{\sqrt5-1}{\sqrt5+1}\)
\(=\cfrac{(\sqrt5+1)^2+(\sqrt5-1)^2}{(\sqrt5-1)(\sqrt5+1)}\)
\(=\cfrac{2[(\sqrt5)^2+(1)^2 ]}{(\sqrt5)^2-(1)^2}\)
\(=\cfrac{2[5+1]}{5-1}\)
\(=\cfrac{12}{4}\)
\(=3\)

\(ab=\cfrac{(\sqrt5+1)}{(\sqrt5-1)}\times\cfrac{(\sqrt5-1)}{(\sqrt5+1)}\)
\(=1\)

\(∴ \cfrac{a^2+ab+b^2}{a^2-ab+b^2}\)
\(=\cfrac{a^2+b^2+ab}{a^2+b^2-ab}\)
\(=(\cfrac{(a+b)^2-2ab+ab}{(a+b)^2-2ab-ab}\)
\(=\cfrac{(a+b)^2-ab}{(a+b)^2-3ab}\)
\(=\cfrac{(3)^2-1}{(3)^2-3×1}\) [\(a+b=3\) এবং \(ab=1\) বসিয়ে]
\(=\cfrac{8}{6}\)
\(=\cfrac{4}{3}\) (Answer)

Similar Questions